24S-Hydroxycholesterol Correlates With Tau and Is Increased in Cerebrospinal Fluid in Parkinson's Disease and Corticobasal Syndrome - Björkhem, Ingemar; Patra, Kalicharan; Boxer, Adam L.; Svenningsson, Per (Frontiers in Neurology, 2018)
24S-hydroxycholesterol (24OHC) and Tau are produced in neuronal cells and neurodegeneration leads to increased flux of both of them into cerebrospinal fluid (CSF). In the present study, CSF levels of 24OHC and 27S-hydroxycholesterol (27OHC) along with those of Tau, P-Thr181-Tau and Aβ42 were measured in patients with early Parkinson´s disease (PD), Corticobasal syndrome (CBS), Corticobasal Degeneration (CBD) and controls. Using mouse models with increased or decreased formation of Tau protein and increased production of 24OHC, we have also tested the hypothesis that there is a direct association between neuronal turnover of 24OHC and Tau. The levels of 24OHC are increased, at a group level, in patients with PD or CBS. We found significant correlations between levels of 24OHC and Tau or P-Thr181-Tau in CSF from patients with PD, CBS or CBD. There were no similar correlations between 24OHC and Aβ42 in CSF from these patients. The neuronal levels of 24OHC were not altered in Tau knockout or Tau overexpressing mice. Vice versa, Tau species levels were not changed in Cyp46 overexpressing mice with increased neuronal levels of 24OHC. We conclude that the strongly correlative fluxes of 24OHC and Tau from neuronal cells to CSF are likely to be secondary to neurodegeneration and not due to direct interaction between the two factors. We suggest that this high correlation reflects a rapid neurodegeneration of specific neuronal subtypes with simultaneous release of 24OHC and Tau into the CSF.